2022
DOI: 10.1098/rstb.2020.0440
|View full text |Cite
|
Sign up to set email alerts
|

Social hierarchies and social networks in humans

Abstract: Across species, social hierarchies are often governed by dominance relations. In humans, where there are multiple culturally valued axes of distinction, social hierarchies can take a variety of forms and need not rest on dominance relations. Consequently, humans navigate multiple domains of status, i.e. relative standing. Importantly, while these hierarchies may be constructed from dyadic interactions, they are often more fundamentally guided by subjective peer evaluations and group perceptions. Researchers ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 229 publications
(263 reference statements)
0
31
0
Order By: Relevance
“…Considerable research has now clearly demonstrated that these dominance hierarchies are a widespread feature of societies occurring broadly across the evolutionary tree ([ 20 , 21 ]; see also Strauss et al . [ 22 ] in this theme issue) including humans (see Redhead & Power [ 23 ] and Zeng et al [ 24 ] in this theme issue).…”
Section: What Have We Learned In the Last Century?mentioning
confidence: 99%
See 3 more Smart Citations
“…Considerable research has now clearly demonstrated that these dominance hierarchies are a widespread feature of societies occurring broadly across the evolutionary tree ([ 20 , 21 ]; see also Strauss et al . [ 22 ] in this theme issue) including humans (see Redhead & Power [ 23 ] and Zeng et al [ 24 ] in this theme issue).…”
Section: What Have We Learned In the Last Century?mentioning
confidence: 99%
“…Dominance therefore describes a dyadic social relationship [ 26 ] that emerges from sequences of agonistic interactions [ 31 ] where one individual exhibits subordination [ 32 ]. Following from this definition, dominance hierarchies are the group-level structure arising from the social network of these dyadic relationships, and although dominance is not a feature of individuals, dominance rank can be a useful measure for summarizing an individual's position in this network (see McCowan et al [ 33 ] and Redhead & Power [ 23 ] in this theme issue).…”
Section: What Have We Learned In the Last Century?mentioning
confidence: 99%
See 2 more Smart Citations
“…Subordinate individuals with similar rank may vary in status-seeking behaviours (e.g. information collecting, prospecting, challenging dominants) that later influence their trajectory in social status [35,[70][71][72]. In summary, to truly understand the influence of rank on fitness and the evolution of status-seeking behaviour, it is necessary to examine dominance trajectories over individuals' lifetime to understand how fitness outcomes vary as a function of rank and mobility over the life course.…”
Section: Individual Level (A) How and Why Do Individuals Change Position In The Dominance Hierarchy?mentioning
confidence: 99%